Individual and joint effects of exposure to phthalates and the risk of cardiovascular disease in the chronic kidney disease population: NHANES 2005–2018 - Yuehong Liang; Xiurong Li (Frontiers in Public Health)
BackgroundThere is a lack of studies on the relationship between urinary phthalate metabolites (UPMs) and cardiovascular disease (CVD) prevalence in adults suffering from chronic kidney disease (CKD). We intended to examine the relationship between UPMs and the prevalence of CVD in people with CKD.MethodsThe research utilized data in the National Health and Nutrition Examination Survey (NHANES) 2005–2018. We employed three statistical models—a generalized linear regression model, a weighted quantile sum (WQS) regression model, and a Bayesian kernel machine regression (BKMR) model.ResultsWe included 834 CKD participants finally. In the generalized linear regression model, the prevalence of CVD was higher in individuals with MiBP (OR 1.86; 95% CI 1.08–3.18; P for trend = 0.022), MCNP (OR 1.85; 95% CI 1.18–2.91; P for trend = 0.011), MBP (OR 1.68; 95% CI 1.02–2.76; P for trend = 0.041) and MECPP (OR 2.22; 95% CI 1.28–3.86; P for trend = 0.008) in the highest tertile compared to those in the lowest tertile. In the WQS model, the WQS index was significantly positively associated with CVD (OR 1.44; 95% CI 1.04–1.99; p value = 0.028). Among the ten phthalates, MCNP showed the highest weight (weighted 0.21). A positive link between phthalate mixture exposure and cardiovascular disease was also demonstrated by the BKMR model. The conditional posterior inclusion probabilities (condPIPs) obtained from the BKMR model indicated that MCNP and MECPP were the primary contributors to the overall effect observed in the group, with condPIP values of 0.581 and 0.508, respectively.ConclusionThe results indicated that phthalate exposure was linked to an elevated risk of cardiovascular disease and highlighted the need to reduce plastic use among the CKD population.